2022
DOI: 10.1021/acs.chemmater.2c03117
|View full text |Cite
|
Sign up to set email alerts
|

Moderate and Universal Synthesis of Undoped Covalent Organic Framework Aerogels for Enhanced Iodine Uptake

Abstract: The fabrication of hierarchically porous covalent organic framework (COF) aerogels is always challenging but of great significance in chemistry and materials science. The known COF aerogel preparation system is very limited and usually results in aerogel composite with low crystallinity. Herein, a universal and moderate synthetic strategy is presented for undoped COF aerogels through the catalysis of scandium trifluoromethanesulfonate. Due to the high catalytic activity of the scandium catalyst on aldimine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…37,70−72 On the other hand, the signal between ∼168 and 170 cm −1 in I 2 @HPOPs is assigned to the stretching vibration of I 5 − . 62,68,73 In general, the absence of peaks above 180 cm −1 in these Raman spectra clearly ruled out the presence of molecular iodine (I 2 ). Overall, the Raman spectra suggested that presence of elemental iodine in I 2 @HPOPs as polyiodide species.…”
Section: ■ Results and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…37,70−72 On the other hand, the signal between ∼168 and 170 cm −1 in I 2 @HPOPs is assigned to the stretching vibration of I 5 − . 62,68,73 In general, the absence of peaks above 180 cm −1 in these Raman spectra clearly ruled out the presence of molecular iodine (I 2 ). Overall, the Raman spectra suggested that presence of elemental iodine in I 2 @HPOPs as polyiodide species.…”
Section: ■ Results and Discussionmentioning
confidence: 71%
“…The Raman spectra of I 2 @HPOPs show three distinct bands that are absent in the as-synthesized sample (Figure S11) of the corresponding HPOPs. The signal between ∼106 and 146 cm –1 in I 2 @HPOPs are assigned to symmetric and asymmetric stretching vibrations in I 3 – species. , On the other hand, the signal between ∼168 and 170 cm –1 in I 2 @HPOPs is assigned to the stretching vibration of I 5 – . ,, In general, the absence of peaks above 180 cm –1 in these Raman spectra clearly ruled out the presence of molecular iodine (I 2 ). Overall, the Raman spectra suggested that presence of elemental iodine in I 2 @HPOPs as polyiodide species.…”
Section: Resultsmentioning
confidence: 82%
“…S25†), which is similar to previous reports. 19,25,55,56 FTIR analysis verified the chemical integrity of the used MC-DMTP–TPB COF (Fig. S26†).…”
Section: Resultsmentioning
confidence: 77%
“… FT-IR profile implied the charge transfer between imine N and iodine molecules, which was further corroborated by XPS analysis. As depicted in Figure A, the I 3d XPS spectra of I 2 @Mw-TFB-BD-CH 3 displayed I 3d 3/2 signals at 630.1 and 631.8 eV as well as I 3d 5/2 signals at 618.5 and 620.1 eV, which were ascribed to the formation of triiodide (I 3 – ) and pentaiodide (I 5 – ) anions. , Based on the integral area of XPS peaks, I 3 – and I 5 – species occupy 46% and 54% of the total I 2 uptake for I 2 @Mw-TFB-BD-CH 3 . In contrast, I 3 – and I 5 – species take up 60% and 40% of the total I 2 uptake for I 2 @Mw-TFB-BD-OCH 3 (Figure B), indicating the pore surface environment affected the polyiodide formation.…”
Section: Resultsmentioning
confidence: 99%